Entropically driven Polymeric Enzyme Inhibitors by End‐Group directed Conjugation. Issue 18 (2nd March 2018) - Hijazi, Montasser; Krumm, Christian; Cinar, Suelyman; Arns, Loana; Alachraf, Wasim; Hiller, Wolf; Schrader, Wolfgang; Winter, Roland; Tiller, Joerg C.
Abstract: A new generic concept for polymeric enzyme inhibitors is presented using the example of poly(2‐methyl‐2‐oxazoline) (PMOx) terminated with an iminodiacetate (IDA) function. These polymers are shown to be non‐competitive inhibitors for horseradish peroxidase (HRP). Mechanistic investigations revealed that the polymer is directed to the protein by its end group and collapses at the surface in an entropy‐driven process as shown by isothermal titration calorimetry. The dissociation constant of the complex was determined as the inhibition constant Ki using HRP kinetic activity measurements. Additional experiments suggest that the polymer does not form a diffusion layer around the protein, but might inhibit by inducing minor conformational changes in the protein. This kind of inhibitor offers new avenues towards designing bioactive compounds. Abstract : Conjugal inhibition : A new generic concept for polymeric enzyme inhibitors is presented using the example of poly(2‐methyloxazoline) terminated with a 2, 2′‐imino diacetate function. These polymers are shown to be non‐competitive inhibitors for horseradish peroxidase (HRP). Mechanistic investigations revealed that the polymer is directed to the protein using the end group, which collapses at the surface in an entropy‐driven process that inhibits the enzyme.